Pengaruh Pinjaman yang Diberikan dan BOPO Pada Profitabilitas dengan Risiko Kredit sebagai Pemoderasi - Dharma Wicaksana, I Gede Hendra; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 27 No 2 (2019), 2019)
Loans provided by banks can be said to be effective and efficient if there is no credit risk, namely bad credit. This study aims to examine the moderation of credit risk to loans and BOPO on the profitability of banks. Profitability in this research is measured using ROA, and loans given are measured by LDR, and efficiency is measured by BOPO. This research is an associative quantitative research. The population of this research is the banking sub-sector of companies listed on the Indonesia Stock Exchange in 2013 d. 2017. This sample was taken using a purposive sampling technique so that the samples obtained were 20 samples of the banking sub-sector companies. The data analysis used is the Moderated Regression Analysis (MRA) test. Based on the results of this study, it was found that credit risk weakened the lending relationship given to profitability and strengthened BOPO's relationship to profitability. Keywords : Given loans, NPL, BOPO